Time for Action - Hill, Keith (Inter Media Group, 2014)
Despite extensive research over the past decade, the rates of falls-related hospitalisations have not reduced. Keith Hill outlines some of the reasons why, and argues for a national commitment to reduce the unacceptably high rate of falls-related deaths and hospitalisations.